Swedish youth football players` attitudes towards moral decision in sport as predicted by the parent-initiated motivational climate - Wagnsson, S.; Stenling, A.; Gustafsson, H.; Augustsson, C. (Psychology of Sport and Exercise, 2016)
Objectives: The purpose of this study was to examine associations between late adolescent football players` perceptions of the motivational climate - as initiated by mothers and fathers - and attitudes towards moral decision making in sports. Design: Cross-sectional. Methods: Participants were 213 Swedish football players (144 males, 67 females) aged 16-19 years who completed measures assessing perceived parent-initiated motivational climate (i.e., success-without-effort climate [SWEC]; worry conducive climate [WCC]; and learning/enjoyment climate [LEC]) and attitudes towards moral decision-making in sport (i.e., acceptance of cheating [AOC]; acceptance of gamesmanship [AOG] and keeping winning in proportion [KWIP]). Results: Canonical correlations demonstrated moderate positive relations between parent-initiated-both mother and father-performance climates (WCC and SWEC) and AOC and AOG. Moreover, the relationship between mother and father-initiated learning/enjoyment climate (LEC) were shown to be moderately and positively associated with the prosocial attitude dimension of KWIP. Results also showed that a mother-initiated LEC and a mother-initiated SWEC were stronger predictors of the criterion variables (AOC, AOG, and KWIP) than equivalent father-initiated climate dimensions. Conclusions: The results highlight the importance of considering the relationship between parent-initiated climates-especially initiated by mothers-and the development of moral decision-making among youth football players.